Unusual thalamic mass and subsequent gelatinous pseudocysts in an immunocompetent host: A case report - Apapatra Akiko Watanabe; Pasin Hemachudha; Wanakorn Rattanawong; Thanakit Pongpitakmetha (My University, 2022)
Cryptococcal meningoencephalitis often occurs in an immunocompromised host with several known neurological manifestations including space-occupying lesions, meningitis or meningoencephalitis. Here, we describe a 38-year-old previously healthy durian farm owner with cryptococcoma and subsequent development of cryptococcus gelatinous pseudocyst after receiving high doses of intravenous dexamethasone to treat mass lesion presumed to be a malignant process. An MRI scan of the head demonstrated a 2-cm heterogeneous solitary enhancing cystic lesion at the right thalamus. Progression of neurological deficit and another repeat imaging showing typical appearance of gelatinous pseudocyst. Lumbar puncture found markedly elevated pressure and cryptococcal antigen strongly positive confirming the diagnosis. He was immediately started on amphotericin B and flucytosine for cryptococcus meningoencephalitis with partial improvement in his vision. This report highlights consideration of cryptococcal infection in an immunocompetent host to avoid delays in diagnosis and treatment.
Keywords: Flucytosine; Fungal Infections and Studies